Pengaruh Green Banking dan Corporate Social Responsibility terhadap Profitabilitas pada Perbankan Syariah di Kawasan ASEAN - Rajuanto, Septian; Fahmi, Muhammad; Helmi, Syarif M (FAKULTAS EKONOMI DAN BISNIS UNTAN, 2026)
Research aims: The side effects of company expansion to increase profits lead to climate change and threats to the sustainability of the ecosystem, thus requiring a